2012
DOI: 10.1080/10962247.2012.700633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activated carbon surface properties on the adsorption of volatile organic compounds

Abstract: Physical and chemical properties of activated carbon (AC) were analyzed to investigate the effects of adsorbate properties on AC adsorption performance. Fixed-bed adsorption experiments were conducted with toluene, acetone, and xylene as adsorbates. From the results, the adsorption capacities of the three adsorbates had the following order: xylene > toluene > acetone. The correlation between experimental data and adsorbate properties was also analyzed. The results showed that different functional groups corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…As observed, the peak area responses of BTEXs were increased with increasing desorption temperature from 225 to 250°C. The BTEX compounds have various boiling points (in the range 80.1–144.4°C at atmospheric pressure), dynamic diameters, vapor pressures and carbon atoms (from six to eight carbon atoms) in their molecular structures (Li, Sun, Li, & Keener, ). Therefore, the desorption temperature has a key role in the desorption efficiency of BTEXs from MIL‐100(Fe)@Fe 3 O 4 @SiO 2 sorbent packed inside NTD, so that the greatest peak area responses of the analytes were observed at 1 min desorption time.…”
Section: Resultsmentioning
confidence: 99%
“…As observed, the peak area responses of BTEXs were increased with increasing desorption temperature from 225 to 250°C. The BTEX compounds have various boiling points (in the range 80.1–144.4°C at atmospheric pressure), dynamic diameters, vapor pressures and carbon atoms (from six to eight carbon atoms) in their molecular structures (Li, Sun, Li, & Keener, ). Therefore, the desorption temperature has a key role in the desorption efficiency of BTEXs from MIL‐100(Fe)@Fe 3 O 4 @SiO 2 sorbent packed inside NTD, so that the greatest peak area responses of the analytes were observed at 1 min desorption time.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption of VOCs on MIL-101 also showed shape selectivity towards VOCs molecules: The adsorption capacity of p-xylene was higher than that of m-xylene and o-xylene even though they have almost equal molecule cross-sectional areas ( Figure 5). It has also been observed that the VOC concentration can have a positive influence on the adsorption capacity of a material [22,72] and that other chemical properties of VOCs such as oxidation state can also influence adsorption.…”
Section: Nature Of Vocsmentioning
confidence: 98%
“…Polar compounds have higher boiling points or lower vapor pressures than non-polar compounds. VOCs, which have a high molecular weight and high boiling point can be effectively adsorbed on AC [72]. At higher boiling points, liquefaction and condensation occur more readily leading to increased adsorption capacity [67,68].…”
Section: Nature Of Vocsmentioning
confidence: 99%
“…• Molecular structure Adsorption capability of organic vapors to the activated carbon increased for the higher molecular weight of the adsorbate [50].…”
Section: Factors Influencing Adsorptionmentioning
confidence: 99%